Spatial Patterns in Baseflow Mean Response Time across a Watershed in the Loess Plateau: Linkage with Land-Use Types. Issue 3 (16th January 2020) - Huang, Xu-dong; Wang, Dong; Han, Pei-pei; Wang, Wen-chuan; Li, Qing-jie; Zhang, Xiao-li; Ma, Ming-wei; Li, Bao-jian; Han, Shi-jie
Abstract: Understanding the relation between land-use types and baseflow mean response time (BMRT) is important to explore the response mechanism of baseflow processes in watersheds. BMRT was determined using an instantaneous unit hydrograph. The instantaneous unit hydrograph parameters were estimated by autocorrelation functions. The relative importance of land-use types in determining BMRT dynamics was assessed by hydrological model and partial least-squares regression. Our study suggests greater effects of urban area on BMRT than the effects of forest and agricultural land. This may be because the urban interception impervious area may impede baseflow generation over a short timescale. The effects of agricultural land are greater than those of forest in areas with steeper hillslopes, but lower than those of the forest in areas with more plains, reflecting the varied ability of forest and agricultural lands with different topography to hinder overland flow. Variations of BMRT are strongly linked to land use in the watershed. Overall, our study provides insight into the BMRT and dominant factors of land-use types in watersheds, planning of sustainable water resource use, and ecological protection in watersheds.